Analysis of Human Resource Management Practices at Putra Jasa Mandiri in Surabaya - Rasendriya, Hera Audita; Khalawatul, Salwa; Aprilliani, Mefy Murtia; Hidayah, Putri Maulidah; Rosmala, Maritza Siiriin; Pramiswari, Trisna Dewi; Fathony, Marsya Sahda; Agustina, Tri Siwi; Barinta , Dunga Dwi (Jurnal Pengabdian West Science, 2025)
This community engagement program aims to enhance human resource management practices at Putra Jasa Mandiri, a small printing microenterprise based in Surabaya. The business struggles with internal issues, such as the lack of structured employee training and the absence of documented Standard Operating Procedures (SOPs). The program's objective is to improve operational efficiency and service quality through two key approaches: implementing comprehensive staff training and developing practical, applicable SOPs. A qualitative method was used, involving direct observation and interviews guided by the 5W+1H technique. The initiative led to positive developments, including better organizational structure, increased employee capabilities, and more consistent service delivery. Furthermore, this program contributes to the realization of SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth), while fostering collaboration between universities and micro, small, and medium enterprises (MSMEs).
Keywords: Community Service; Employee Training; MSMEs Empowerment; SDGs; SOP